Dari Literasi Keuangan menuju Kesejahteraan Finansial: Peran Mediasi Perilaku Keuangan dan Inklusi Keuangan dalam Era Ekonomi Digital - Verra Rosyalia Widia Sofyan; Rangga Munggaran; Rama Nugraha Irawan Surayuda (Jurnal Ekonomi Bisnis dan Manajemen, 2026)
The gap between financial literacy and financial well-being in Indonesia remains a structural issue amidst the rapid transformation of the digital economy. This study aims to examine the effect of financial literacy on financial well-being, with financial behavior and financial inclusion as mediating variables in the context of the digital economy era. A quantitative approach with a cross-sectional survey design was applied to 200 productive-age respondents who use digital financial services in Indonesia, selected through a purposive sampling technique. Data analysis used Partial Least Squares – Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software with a bootstrapping procedure of 5,000 subsamples. The test results proved that financial literacy had a positive and significant direct effect on financial well-being (β = 0.241; p = 0.001). Financial behavior was shown to significantly mediate this relationship (β = 0.149; p = 0.002), as was digital financial inclusion (β = 0.114; p = 0.004). The multiple mediation model yielded an R² value of 0.614, indicating that the two mediators were able to explain 61.4% of the variation in respondents' financial well-being. This finding implies that policies to improve public financial well-being must be designed in an integrated manner, encompassing strengthening literacy, developing responsible financial behavior, and expanding access to inclusive digital financial services.